Hospitalized muslim trauma patients ibadah disability scale (HM[T]- IDS): Validation and reliability testing - Mohd Ariff, Sharifudin; Abd Latif, Arifin; Nur Azree Ferdaus, Kamudin; Yuzana, Mohd Yusop; Mai Nurul Ashikin, Taib; Wan Rumaizi, W. Husin; Mohd Adham, Shah Ayeop; Mohd Nazri, Mohd Yusof (2021)
Introduction: The HM[T]-10S is a bilingual, physician reported assessment tool, desired as a standard, objective evaluation scoring system to recognize disability levels of Muslim trauma patients during hospitalization in performing religious physical cleansing and prayer, thus improve the deliverance of assistance they need. It is constructed based on both patients' and physicians perspectives of difficulties et performing religious duties. The assessment is based on five domains: a) pain, b) mobility, c) extremity Involvement, d) bandage/ cast application, and e) touting, and utilizes a Linker, scale based on severity of the disabilities/ difficulties. From the total score given, patients are categorized (Category I-NI based on the assistance required. We aimed to validate and test its reliability .1 practice_ Methodology: Panels of experts were involved in the face and content validations. The inter-observer reliabilities were evaluated between raters of im tar and different levels of qualification (specialism, medical officers, housemen, and nurses). Parallel-forms re liability was evaluated between the scoring using different languages by the same raters. Cohen's or Fleiss' kappa statistics was calculated for ordinal variables (items of the scoring system) and intraclass correlation coefficient was calculated for continuous variables (total score of patients). Internal consistency was measured using Cronbach's alpha. Results: 100 Muslim trauma patents were recruited for the study. Statistical analyses showed moderate (k 0.40 to 059) to almost perfect agreement (k.0 80 to 1.00) in almost all domains, except some fair agreement (ke0.20 to 0 39) for pain and bandage application. Cronbadt's alpha ranged between 0.800 and 0.900 indicating good internal consistency. Conclusions: The proposed system provides a new practical measure to evaluate disability among Muslim patients in performing their religious duties. It will provide a balance approach in trauma patient' care. It is not %About limitations and further research work on be focused on implementing it at other institutions.